2022
DOI: 10.1177/01461672221085797
|View full text |Cite
|
Sign up to set email alerts
|

Routines and Meaning in Life: Does Activity Content or Context Matter?

Abstract: People feel that their lives are more meaningful while engaging in behaviors more closely aligned with their routines. Does the behavioral content of these routines and the contextual factors surrounding their enactment matter for this relationship? In two experience sampling studies ( N = 93, 1,512 episodes; N = 97, 1,629 episodes), we test whether the relationship between routines and meaning in life (MIL) depends on the content of the activities. We found that the degree to which one’s current activity is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 70 publications
(78 reference statements)
2
12
0
Order By: Relevance
“…Similarly, data from ESM surveys sent to participants six times per day for seven days showed that the degree to which participants' current activity was part of a routine positively related to concurrent feelings of meaning in life . These findings were replicated in two additional studies (Mohideen & Heintzelman, 2022), which used a similar design, with participants completing three ESM surveys per day for seven days. In these studies, the degree to which a current behavior was a part of a routine positively predicted meaning in life regardless of whether the behavior was linked to other meaningful features of the activity like the degree to which it fostered relationships, goals, or prosociality (Mohideen & Heintzelman, 2022).…”
Section: What Predicts Meaning In Life Within Person?mentioning
confidence: 63%
See 4 more Smart Citations
“…Similarly, data from ESM surveys sent to participants six times per day for seven days showed that the degree to which participants' current activity was part of a routine positively related to concurrent feelings of meaning in life . These findings were replicated in two additional studies (Mohideen & Heintzelman, 2022), which used a similar design, with participants completing three ESM surveys per day for seven days. In these studies, the degree to which a current behavior was a part of a routine positively predicted meaning in life regardless of whether the behavior was linked to other meaningful features of the activity like the degree to which it fostered relationships, goals, or prosociality (Mohideen & Heintzelman, 2022).…”
Section: What Predicts Meaning In Life Within Person?mentioning
confidence: 63%
“…These findings were replicated in two additional studies (Mohideen & Heintzelman, 2022), which used a similar design, with participants completing three ESM surveys per day for seven days. In these studies, the degree to which a current behavior was a part of a routine positively predicted meaning in life regardless of whether the behavior was linked to other meaningful features of the activity like the degree to which it fostered relationships, goals, or prosociality (Mohideen & Heintzelman, 2022). In other words, engagement in even mundane routines predicted feelings of meaning in life.…”
Section: What Predicts Meaning In Life Within Person?mentioning
confidence: 63%
See 3 more Smart Citations